THE REFLECTION OF THE PHENOMENON OF FREEDOM OF CONSCIENCE AND THE PRINCIPLE OF INTERRELIGIOUS TOLERANCE IN THE LEGISLATION OF THE INTERNATIONAL COMMUNITY AND UZBEKISTAN - Toshpulotov Shokhijakhon Eshpulotovich (International Journal of Innovations in Engineering Research and Technology, 2021)
This article analyzes the problems of ensuring religious tolerance, particularly freedom of conscience, which is one of the main features of a judicial democratic state based on the sign of law. Also revealed the correlation between the norms of international law and the national legislation of the Republic of Uzbekistan in the establishment of tolerant relations in the religious sphere.